Interpreting Communicative Language Teaching: CONTEXTS AND CONCERNS IN TEACHER EDUCATION - SANDRA J. SAVIGNON (Yale University Press, 2002)
In the literature on communicative language teaching, or CLT, teacher education has not received adequate attention. My purpose in conceiving and editing this volume was to bring together a horizon-broadening variety of initiatives, projects, and activities related to teacher education that can make language teaching communicative in the broadest, most meaningful sense. The collection showcases some of the best work being done internationally to make CLT an attainable goal. Ordering the chapters was a challenge. Themes appear and reappear, voices heard in one text are echoed in another. These links and recurrences contribute significantly to the cohesion and strength of the collection. As editor I have taken a hands-oâˆš approach to shaping individual chapters, striving, rather, to preserve the unique, contextualized perspective of each contributing author. Together, the contributors oâˆšer thought-provoking insights into the construct of CLT, as it has come to be known worldwide, and provide practical examples for meeting the challenges of educating language teachers in the new millennium. For the most part, the chapter authors look at CLT from the perspective of practicing teachers. The impression throughout is one of hearing voices from the classroom. In some chapters, we hear from teacher educators, research-ers, and national policy makers, in addition to teachers. The result is a vivid representation of language teaching as the collaborative and context-specific human activity that it is.